The full-time school: a study concerning the Portuguese public school - Fonseca, Dora Sofia Ramos (2021)
The “Full-Time School” Program was implemented in Portugal, starting in 2006, through the “Curriculum Enrichment Activities” (CEA) which, according to the political-normative discourse, intended to increase the length of stay of children in schools in the 1st cycle of Basic Education, in order to articulate the school functioning with the family’s needs, but, at the same time, provide students with opportunities for their global and diversified training. About this context, this work seeks not only to understand how educational organizations fulfilled, in their action, the demands of central power, but also to question whether the pedagogical dynamics corresponded to the children’s needs and interests, contributing for their global and balanced development. Methodologically, we conducted the investigation by associating document analysis and meta-analysis of studies on the reality of the Portuguese school context with the case study developed in an educational organization (Grupamento de Escolas Aventura). We concluded that the “Full-Time School” Program was configured, especially, as a solution for the occupation of the times when parents cannot be with their children, not responding to the children's effective interests and needs. The long stay at school in overly oriented activities does not seem to contribute pedagogically rich for them, in order to contribute to the global and balanced development of children.